Analisis Postur Kerja Pada Karyawan UD Berkah Gemilang Magetan Menggunakan Metode Rapid Upper Limb Assessment (RULA) - Ichsan, Taufiq; Hendrawan, Aloysius Tommy; Untari, Erny (Jurnal TRINISTIK: Jurnal Teknik Industri, Bisnis Digital, dan Teknik Logistik, 2023)
This research was conducted at UD Berkah Gemilang Magetan bread UMKM. UD Berkah Gemilang is an MSME that operates in the food industry whose products are bakpia, sponge cake and peanut bread. This research aims to determine the internal and external conditions that are occurring within UD Berkah Gemilang. This study also analyzes the posture of workers at UD Berkah Gemilang, this analysis is expected to minimize serious injuries to workers at UD Berkah Gemilang Magetan. This research uses the RULA method, with data collection techniques using observation and documentation methods. From the results of the analysis, it was found that the position of workers in the bread dough process section is very dangerous and there must be improvement to avoid excessive muscle injury. In this study, the working posture of the body parts at UMKM UD Berkah Gemilang was evaluated using the RULA (Rapid Upper Limb Assessment) method. Based on the score for the workers' body posture in the bread dough process, it is 6, which means that further investigation will change immediately. Meanwhile, the working posture oven process received a score of 4, which means further investigation and changes may be needed.